"Truce um triângulo no matulão [...] xote, maracatu e baião": a musicalidade de Luiz Gonzaga na construção da "identidade" nordestina - Moraes, Jonas Rodrigues de (2009)
The discussion about the Northeast and the political division of the country regionalization take part in the pathways institutors of history dynamics as a debate that goes beyond all discourses and power circles present in academic, politic, artistic, and literary points of view. This context has provided the structural elements of what can be called the invention or reinvention of spatial identities, place, the northeast region, and subject, the northeastern people. This dissertation discusses the musical production and the artistic trajectory of Luis Gonzaga, precisely with his invention of the baião and other genres that are appropriated by the accordionist, which served as structural discourses of the referred identity markers of a northeastern identity. The analysis of the songs (lyrics and rhythms) and the performance of the author served as discursive tactics for the construction of a northeastern imaginary. The baião and other genres played by a stage performance organization, called musical trio, forged a type of music which embedded itself naturally in the processes of identity negotiability with its audience. The discursive translation of northeast and northeastern people was also engendered through images and symbols retrieved from garments of regional traditions (the bandits and the cowboys) and reassigned meaning by the artist within a socially urban context.The musicality of Gonzaga was constructed in an intersection between the northeastern backwoods (backlands) and the urban centers (the civilized lands). His production of sounds, themes, and acoustic culture combined were linked to the northeastern regionalism. Gonzaga s music had the capacity to express a sense of northeastern identity (northeasternity or nordestinidade) which reverberated and found resonance in its audience (listeners/receivers). The analysis of the songs was systematically organized seeking to observe the themes that demonstrated and corroborated with the identity landmarks in regards to the northeastern territoriality. It should be noted that the use of such themes was genuinely related to social experiences lived and Gonzaga s musicality so that the themes presented in his repertoire were: drought, suffering, homesickness/nostalgia, baião, backwoods/backlands (countryside), aboio (the cry of the Brazilian cowboy), and cowboy among others. It is a dissertation examined within the perspective of Cultural History, approaching in its theoretical aspects the conceptual categories of identity, traditions, acoustic culture, social imaginary, performance, rural/urban, territory, images, cultural resistance and preservation, national-popular, hybridization, and other rhythms referenced in consonance with the ways of living, the symbolic values, customs and musical artistry. Finally, this work was constructed in a relationship of history with music and its forms of interpretation